Outcomes Associated With Inferior Vena Cava Filters Among Patients With Thromboembolic Recurrence During Anticoagulant Therapy. - Mellado M; Pijoan JI; Jiménez D; Muriel A; Aujesky D; Bertoletti L; Decousus H; Barrios D; Clará A; Yusen RD; Monreal M; RIETE Investigators; et al. (Elsevier, 2016)
Objectives: The aim of this study was to assess the effectiveness of inferior vena cava (IVC) filter use among patients who develop recurrent symptomatic venous thromboembolism (VTE) on anticoagulant therapy. Background: There is a lack of efficacy evidence of IVC filter therapy in patients with VTE recurrence on anticoagulant therapy. Methods: In this cohort study of patients with acute VTE identified from the RIETE (Registro Informatizado de la Enfermedad Tromboembólica) registry, the associations between IVC filter placement for VTE recurrence in the first 3 months of anticoagulant therapy and the outcomes of all-cause mortality, pulmonary embolism (PE)-related mortality, second recurrent VTE, and major bleeding rates through 30 days after diagnosis of recurrence were assessed. Results: Among 17 patients treated with filters and 49 matched patients treated without filters for VTE recurrence that presented as deep vein thrombosis, propensity score-matched groups showed no significant differences in death for filter insertion compared with no insertion (17.7% vs. 12.2%; p = 0.56). Among 48 patients treated with filters and 91 matched patients treated without filters for VTE recurrence that presented as PE, propensity score-matched groups showed a significant decrease in all-cause death for filter insertion compared with no insertion (2.1% vs. 25.3%; p = 0.02). The PE-related mortality rate was not significantly lower for filter insertion than no insertion (2.1% vs. 17.6%; p = 0.08), though the point estimates markedly differed. Conclusions: Among patients with VTE recurrence during the first 3 months of anticoagulant therapy, IVC filter insertion was not associated with a survival benefit in patients who recurred with deep vein thrombosis, although it was associated with a lower risk for all-cause death in patients who recurred with PE.